takeout, a novel Drosophila gene under circadian clock transcriptional regulation. - So, W.V.; Sarov-Blat, L.; Kotarski, C.K.; McDonald, M.J.; Allada, R.; Rosbash, M. (Molecular and Cellular Biology, 2000)
We report the identification and characterization of a new Drosophila clock-regulated gene, takeout (to). to is a member of a novel gene family and is implicated in circadian control of feeding behavior. Its gene expression is down-regulated in all of the clock mutants tested. In wild-type flies, to mRNA exhibits daily cycling expression but with a novel phase, delayed relative to those of the better-characterized clock mRNAs, period and timeless. The E-box-containing sequence in the to promoter shows impressive similarities with those of period and timeless. However, our results suggest that the E box is not involved in the amplitude and phase of the transcriptional cycling of to. The circadian delayed transcriptional phase is therefore most likely the result of indirect regulation through unknown transcription factors.